Evidence for sequential performance effects in professional darts - Stins, J.; Yaari, G.; Wijmer, K.; Burger, J.; Beek, PO. (Frontiers in Psychology, 2018)
Objectives: The study of sequential effects in aiming tasks might shed light on the organization of repetitive motor performances over time. To date, investigations of such effects in sports have been limited and yielded mixed results. Given the relatively short time intervals between successive attempts, and the absence of defensive interventions, dart throwing provides a potentially fruitful testing ground for examining the presence of sequential performance effects in the motor domain.